Testing correlation between vertical crustal movements and geoid uplift for North Eastern Polish border areas - Kowalczyk, Kamil; Kuczynska-Siehien, Joanna (International Conference “Environmental Engineering”, 2017)
Long time span of observations from GNSS permanent stations can be used in the development of models of vertical crustal movements. The absolute vertical crustal movement related to the ellipsoid consists of the observed movement with relation to the mean sea level, the eustatic movement and the geoid uplift. The geoid uplift can be determined from GRACE satellite mission observations. The calculated parameters can be compared with the theoretical ones. The aim of this study is to check the correlation between vertical crustal movements and a geoid height variations determined from satellite data. GNSS data, levelling data and satellite observations for north eastern Polish border areas were used as a case study. Temporal variations of geoid were calculated based on the geopotential models from GRACE satellite observations. The obtained results give an overview of a possibility of the proposed method usage.